2019
DOI: 10.1111/tri.13536
|View full text |Cite
|
Sign up to set email alerts
|

Everolimus enhances TRAIL‐mediated anti‐tumor activity of liver resident natural killer cells in mice

Abstract: Summary In transplantation, innate immunity plays a pivotal role in immunosurveillance and host defence against microbes and neoplastic cells. Liver‐resident NK cells express TNF‐related apoptosis‐inducing ligand (TRAIL), which distinguishes them from conventional NK cells. In this study, we investigated the impact of mTOR inhibition on liver‐resident NK cells in comparison with that on splenic NK cells in a mouse model. In mice that received everolimus (EVR) for 7 days (range: 0.0125–0.25 mg/kg/day), the prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 36 publications
4
12
0
Order By: Relevance
“…Considering the possible negative effects of LPLC-induced liver regeneration during chronic liver disease, such as liver fibrosis and hepatocarcinoma, NK cells have also been researched in such diseases. Recently, Saparbay et al 83 have demonstrated that the treatment of Everolimus could enhance the antitumor activity of immature liver-resident NK cells through the up-regulation of tumor necrosis factor-related apoptosis-inducing ligand (TRAIL), consistent with an earlier study showing that liver-resident NK cells were distinctly characterized by expression of TRAIL, 84 which could attack virus-infected and tumor cells. 85 For liver fibrosis, NK cells could kill activated HSCs via RAE1/NKG2D- and TRAIL-dependent mechanisms, thereby controlling and ameliorating liver fibrosis, 86 indicating the important role of NK cells in suppressing liver fibrosis during hepatitis B virus or hepatitis C virus.…”
Section: Liver Regeneration In Chronic Liver Diseasessupporting
confidence: 69%
“…Considering the possible negative effects of LPLC-induced liver regeneration during chronic liver disease, such as liver fibrosis and hepatocarcinoma, NK cells have also been researched in such diseases. Recently, Saparbay et al 83 have demonstrated that the treatment of Everolimus could enhance the antitumor activity of immature liver-resident NK cells through the up-regulation of tumor necrosis factor-related apoptosis-inducing ligand (TRAIL), consistent with an earlier study showing that liver-resident NK cells were distinctly characterized by expression of TRAIL, 84 which could attack virus-infected and tumor cells. 85 For liver fibrosis, NK cells could kill activated HSCs via RAE1/NKG2D- and TRAIL-dependent mechanisms, thereby controlling and ameliorating liver fibrosis, 86 indicating the important role of NK cells in suppressing liver fibrosis during hepatitis B virus or hepatitis C virus.…”
Section: Liver Regeneration In Chronic Liver Diseasessupporting
confidence: 69%
“…Currently, increasing studies have identified various receptor-ligand signals between NK cells and their target cells ( 21 ), and several crucial signals will be discussed below. The activated NK cells kill the target cells through several mechanisms: granule exocytosis, death receptor-mediated apoptosis ( 22 , 23 ), and cytokine secretion ( 24 ). Thus, activation of NK cells is expected to becoming a promising strategy to halt the progression of liver diseases.…”
Section: Nk Cells In the Livermentioning
confidence: 99%
“…Fortunately, IL-15 could recover HCC-induced liver-resident NK-cell dysfunction [37] . In addition, the mTOR inhibitor -everolimus -enhances their anticancer activity through upregulation of TRAIL [39] . Thus, liver-resident NK cells have the potential for application in HCC therapy, although the complete underlying mechanism of liver-resident NK cells' exhaustion remains unclear.…”
Section: Nk Cells In Hccmentioning
confidence: 99%